Factors That Affect Consumers Using the GO-JEK GO-FOOD Feature Aplication (Study on Students of Makassar State University Faculty of Social Sciences Business Administration Study Program) - Afwa Magfhirah Saleh; Firman Umar; Muh Rizal; Maya Kasmita; Muh Luthfi Siraj (Universitas Negeri Makassar, 2021)
Go-food is a service feature provided in the Go-jek application that serves food delivery service. Go-food comes as a solution for city communities that have high mobility, time constraints, and high need for food is now able to be resolved with the existence of Go-food.The purpose of this study is to find out how strong factors in influencing and knowing from several factors which are most dominant in decision making using the Go-jek go-food feature application in students majoring in business administration of the faculty of social sciences. The type of method used is descriptive quantitative. The data source is primary data, data processing using SPSS 25. Samples from this study were taken by 100 respondents. Sampling techniques are purposive sampling. Data retrieval techniques are carried out by coesioner and observation. Data analysis techniques used with descriptive statistical analysis and inferential analysis. The results of this study show factors: distribution, promotion and culture have a significant effect / very strong. The most dominant factor in influencing the decision to use the Go-jek go-food feature is the promotion factor which has a value percentage of 0.441.